Development of SKORLP Four Tier Test Form Diagnostic Test Instruments to Identify Conception Profiles of Parallel Electrical Circuits - Reza Hesti (Universitas Islam Negeri (UIN) Mataram, 2022)
Researchers developed the Parallel Electrical Circuit Online Conceptual Survey (SKORLP) instrument into a four-tier diagnostic test. The purpose of the study was as a first step in the development of the SKORLP four-level test format into a diagnostic test instrument on Parallel Electrical Circuit materials. The research method used is a 4D model (Defining, Designing, Developing, and Disseminating). The instrument developed has been tested on 23 students in one of the MTs of South Jakarta. From the results of the study, it was found that the development of SKORLP in the form of a four-tier test allows it to be presented online and has great potential in producing student conception profiles in the parallel electrical circuit material, that is, students who understand the concept of Sound Understanding (SU), understand but partially or Partial Understanding (PU), misconceptions or Misconceptions (MC), do not understand the concept of Parallel Electrical Circuits at all or No Understanding (NU).